2013
DOI: 10.1371/journal.pone.0079478
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the PI3K/Akt/GSK3 Pathway Downstream of BCR/ABL, Jak2-V617F, or FLT3-ITD Downregulates DNA Damage-Induced Chk1 Activation as Well as G2/M Arrest and Prominently Enhances Induction of Apoptosis

Abstract: Constitutively-activated tyrosine kinase mutants, such as BCR/ABL, FLT3-ITD, and Jak2-V617F, play important roles in pathogenesis of hematopoietic malignancies and in acquisition of therapy resistance. We previously found that hematopoietic cytokines enhance activation of the checkpoint kinase Chk1 in DNA-damaged hematopoietic cells by inactivating GSK3 through the PI3K/Akt signaling pathway to inhibit apoptosis. Here we examine the possibility that the kinase mutants may also protect DNA-damaged cells by enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 41 publications
8
32
0
1
Order By: Relevance
“…To test the possible involvement of p53 in these processes, we examined Ton.32D/pRevTRE-p53-DD cells. In accordance with our previous reports [16, 17], inhibition of Jak2 by JakI-1 prevented etoposide-induced accumulation of these cells in the G2/M phase and drastically enhanced apoptosis, as shown in Figure 2A. Very similar results were obtained by using the Jak1/Jak2 inhibitor ruxolitinib clinically in use for myeloproliferative neoplasms (Supplementary Figure S2) [15].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…To test the possible involvement of p53 in these processes, we examined Ton.32D/pRevTRE-p53-DD cells. In accordance with our previous reports [16, 17], inhibition of Jak2 by JakI-1 prevented etoposide-induced accumulation of these cells in the G2/M phase and drastically enhanced apoptosis, as shown in Figure 2A. Very similar results were obtained by using the Jak1/Jak2 inhibitor ruxolitinib clinically in use for myeloproliferative neoplasms (Supplementary Figure S2) [15].…”
Section: Resultssupporting
confidence: 92%
“…We have previously shown that inhibition of cytokine-induced activation of Jak2 signaling pathway induces apoptosis synergistically with chemotherapeutics in hematopoietic cells by down regulating Chk1-mediated G2/M checkpoint activation through mechanisms involving activation of GSK3 [16, 17]. To test the possible involvement of p53 in these processes, we examined Ton.32D/pRevTRE-p53-DD cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another area of investigation is the hypoxic bone marrow niche, as demonstrated by Konopleva et al 73,74 . Multiple studies have suggested that dual inhibition of both PI3K and FLT3 may serve as a means of overcoming resistance of the bone marrow stroma as a protective environment for leukemic cells, and should be further investigated as a novel therapeutic approach in patients with FLT3 -mutated AML 75,76 . Another potential mechanism of acquired resistance to FLT3 kinase inhibitors is the development of point mutations in the kinase domain, notably the FLT3 D835 point mutation 77 .…”
Section: Expert Opinionmentioning
confidence: 99%